Recovery markers in elite climbers after the national boulder climbing championship - Gáspari, Arthur Fernandes; Zaminiani, Mayni Gabriele; Vilarinho, Manoela de Carvalho; Caruso, Danilo; Guimarães, Patricia dos Santos; Piunti, Rafael Perlotti; Itaborahy, Alex; de Moraes, Antonio Carlos (Frontiers in Sports and Active Living, 2024)
This study aimed to investigate recovery markers among elite climbers following the Boulder Nationals competition. We assessed maximum isometric hand grip strength (HS), forearm swelling (circumference), delayed soreness in forearm muscles, tiredness, and exercise readiness at several time points: pre-competition, immediately post-competition (within 4 minutes after their last effort), as well as at 12, 24, 48, and 60 hours post-competition. Maximum isometric hand grip strength decreased by 6.38 ± 1.32% (p = 0.006) post-12h, returning to pre-competition values post-24h (all p > 0.05). Forearm circumference (FC) increased 1.78 ± 1.77% (p < 0.001) post-competition, returning to pre-competition values post-12h (all p > 0.05). Forearm pain (FP) increased post-competition (p = 0.002) and post-12h (p < 0.001), returning to pre-competition values post-24h (all p > 0.05). Tiredness increased post-competition (p < 0.001), post-12h (p < 0.001) and post-24h (p < 0.001), returning to pre-competition values post-48h (all p > 0.05). Climbing readiness was reduced post-competition (p < 0.001), post-12h (p < 0.001), post-24h (p < 0.001) and post-48h (p = 0.005), only returning to pre-competition values post-60h (p = 0.189). Visual analysis of individual data points out a relatively small variability in the HS and FC markers, while FP, tiredness, and readiness exhibit larger individual variations. These findings indicate that different recovery patterns exist for the analyzed markers, suggesting that athletes may require up to 60 hours after the competition to fully recover and regain their ability to face new competitive challenges.